Deficyt demokratyczny w Unii Europejskiej - Mizera, Kamila (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The main idea of this article is to show the concept of EU democracy. At every stage of the European integration process, the question of democratic legitimacy has become increasingly sensitive. The principle of democracy and legitimation are the most acute issues in international organizations. It is important to find the answers to fundamental questions like: what is the source of legitimation, is the European Union a democratic or an undemocratic organization, how to define the term “democratic deficit” and how to overcome lack of the democracy at different levels of EU power. It is essential to estimate the impact of democratic deficit in EU development, to examine what constitutes a democratic deficit, to analyze whether there is one in the EU, and to offer suggestions for a solution. Is the democratic deficit another myth propagated by Eurosceptic circles? In this article I want to emphasize the meaning of the executive and the role of basic principles like the principle of subsidiarity or the principle of proportionality.
Keywords: Unia Europejska; deficyt demokratyczny; demokracja; legitymizacja władzy; parlamenty narodowe